Gamification in Science Learning to Improve Student Literacy - Nur Annisaa Septiani; Rosita Putri Rahmi Haerani; Erna Suhartini (Scientiae Educatia: Jurnal Pendidikan Sains)
This research is based on students' low science literacy skills based on the results of research conducted by the Program for International Student Assessment (PISA) in 2022. This study aims to determine the effectiveness of educational game-based science learning on students' science literacy. This educational game development uses the Research and development method with the ADDIE development model (analysis, design, development, implementation, evaluation), producing an educational game that can be accessed without an application. Data is collected by providing feasibility instruments, observation sheets, test questions, and questionnaires. This educational game has been assessed for feasibility by 2 material experts, with a score of 90% in the very feasible category, and 2 media experts, 88% in the very feasible category. The feasibility test was also conducted through a small-scale trial of 96% very feasible category. The student feasibility assessment on a large-scale trial with 28 respondents obtained a value of 94% in the very feasible category, and a feasibility assessment from the teacher was obtained in the 98% very feasible category. The n-gain test results showed an increase of 0.573 with a moderate category. Using this educational game in learning can improve students' science literacy.